2016
DOI: 10.1016/j.ssi.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cobalt doping on the morphology and electrochemical performance of high-voltage spinel LiNi0.5Mn1.5O4 cathode material

Abstract: To reveal the effect of Co-doping on the electrochemical performance of micro-sized LiNi 0.5 Mn 1.5 O 4 (LNMO), undoped LNMO and Co-doped LiCo 0.1 Ni 0.45 Mn 1.45 O 4 (LCoNMO) are synthesized via a PVP-combustion method and calcined at 1000 °C for 6h. SEM and XRD analyses suggest that Co-doping decreases the particle size and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Many metallic elements have been investigated to dope LNMO materials, including transition‐metal ions, such as Ti 4+ , [ 60 ] V 5+ , [ 61 ] Cr 3+ , [ 62 ] Fe 3+ , [ 63 ] Co 3+ , [ 64 ] Cu 2+ , [ 65 ] Zn 2+ , [ 66 ] Zr 4+ , [ 67 ] Nb 5+ , [ 68 ] Mo 6+ , [ 69 ] Ru 4+ , [ 70 ] and Sm 3+ , [ 71 ] and non‐transition‐metal ions, such as Na + , [ 72 ] Mg 2+ , [ 73 ] Sr 2+ , [ 74 ] Al 3+ , [ 75 ] and Ga 3+ . [ 76 ]…”
Section: Approaches To Improve the Cycling Stability Of Lnmomentioning
confidence: 99%
See 2 more Smart Citations
“…Many metallic elements have been investigated to dope LNMO materials, including transition‐metal ions, such as Ti 4+ , [ 60 ] V 5+ , [ 61 ] Cr 3+ , [ 62 ] Fe 3+ , [ 63 ] Co 3+ , [ 64 ] Cu 2+ , [ 65 ] Zn 2+ , [ 66 ] Zr 4+ , [ 67 ] Nb 5+ , [ 68 ] Mo 6+ , [ 69 ] Ru 4+ , [ 70 ] and Sm 3+ , [ 71 ] and non‐transition‐metal ions, such as Na + , [ 72 ] Mg 2+ , [ 73 ] Sr 2+ , [ 74 ] Al 3+ , [ 75 ] and Ga 3+ . [ 76 ]…”
Section: Approaches To Improve the Cycling Stability Of Lnmomentioning
confidence: 99%
“…Reproduced with permission. [ 64 ] Copyright 2016, Elsevier Publisher. d) Voltage profiles of LiNi 0.5 Mn 1.5‐ x Ti x O 4 /graphite full‐cells at 45 ° C. Reproduced with permission.…”
Section: Approaches To Improve the Cycling Stability Of Lnmomentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported a polyvinylpyrrolidone (PVP)-combustion method. With this method, we prepared some TMO materials for Li-ion and Na-ion batteries with high rate capability and cycling stability [26][27][28][29][30] . PVP can fix metal ion on the macromolecular chain via chelation, so the precursor is very uniform which benefits good electrochemical performance.…”
Section: P2-type Na 2/3 Ni 1/3 Mn 2/3 O 2 Is An Air-stable Compound Bmentioning
confidence: 99%
“…Co doping is an effective way to eliminate the Li x Ni 1– x O impurity and provide a more stable spinel structure with enhanced disorder of the cations in the octahedral sites. It has also been reported that the amount of Co doping can significantly affect the electrochemical performance. ,,, Co-doped LiNi x Co y Mn z O 4 cathode materials exhibit excellent electrochemical performances when the amount of Co doping is appropriate ( y ≈ 0.1). ,, However, the electrochemical performances of Co-doped LiNi x Co y Mn z O 4 are not significantly different from those of LiN i0.5 Mn 1.5 O 4 when the amount of Co doping is reduce to a low degree ( y ≤ 0.05). , Therefore, in this study, spherical agglomerations of octahedral single-crystalline LiNi 0.5 Co 4 x Mn 1.5–3 x O 4 cathode materials ( x = 0.02 and 0.03) with exposed planes were prepared by hydroxide coprecipitation in an 8-L continuous reaction device (Figure ) using a combinational postannealing method. The electrochemical performances of conventional spherical LiNi 0.5 Mn 1.5 O 4 particles and spherical agglomerations of octahedral Co-doped LiNi 0.5 Co 4 x Mn 1.5–3 x O 4 cathode materials prepared by the same method were compared.…”
Section: Introductionmentioning
confidence: 99%